2019
DOI: 10.1111/cid.12778
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic indices around narrow diameter implants placed in different glycemic‐level patients

Abstract: Background: Studies assessing peri-implant clinical and marginal bone resorption (MBR) around narrow diameter implants (NDIs) placed in different glycemic levels are uninvestigated. Objective: The present 3-year retrospective follow-up investigation was designed to explore clinical and radiographic status of NDIs placed in individuals with different glycemic control levels. Materials and Methods: Patients with serum hemoglobin A1c (HbA1c) levels ≥6.5% (Group-1), 5.7%-6.4% (Group-2), and 4.0%-5.0% (Group-3) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ten studies found that implant failure was more frequent in non-diabetics but was not statistically significant (Alsaadi et al, 2008; Anner et al, 2010; Bell et al, 2011; Busenlechner et al, 2014; Doyle et al, 2007; Keller et al, 1999; Le et al, 2013; Levin et al, 2011; Oates et al, 2014; van Steenberghe et al, 2002). In addition, seven studies found that all diabetics and non-diabetics retained their implant during the study (Al Amri et al, 2016; Alsahhaf et al, 2019; Al□Shibani et al, 2019; Dowell et al, 2007; Erdogan et al, 2015; Gómez-Moreno et al, 2015; Sundar et al, 2019). In six studies that performed the resonance frequency analysis, no statistically significant difference was found between diabetics and non-diabetics (Al Zahrani & Al Mutairi, 2018; Erdogan et al, 2015; Ghiraldini et al, 2016; Oates et al, 2009, 2014; Sundar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…All the seven included studies were prospective clinical studies whose results were published between 2014 and 2021 and featured a maximum three-year follow-up period. The total number of patients with diabetes (DM) recruited for the included studies was 280, and 166 for the control group (Non-DM-patients without diabetes), with a maximum mean age for the study of Tatarakis et al (2014) [26] group DM 65 ± 8.9 (51-80) and minimum for the study of Alsahhaf et al [32] (2019) Non-DM group 43.4 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The total number of implants placed in the DM groups was 343 while for the Non-DM group it was 212.…”
Section: Data Characteristicsmentioning
confidence: 99%
“…The total number of implants placed in the DM groups was 343 while for the Non-DM group it was 212. The studies that report data for a follow-up period of only six months were three: 2019) [32].…”
Section: Data Characteristicsmentioning
confidence: 99%